GLOBALIZATION OF THE WORLD ECONOMY AND THE WORLD FINANCIAL CRISIS - Y. I. Kendyukh,; I.G. Kendyukh,; O.A. Tsapova,; N.Yi. Mikhailova, (Academic Journal of Physical and Chemical Sciences, 2019)
Any national economy is part of the global economic system, which appears as a set of interconnected and interacting with each other national-state economic systems. This mutual influence is reflected in all countries of the world, about which this article describes in detail, a forecast is made for future years regarding the upcoming crisis, and the reasons for its occurrence are presented. According to the authors, the fact that in the entire sphere of socio-economic globalization it has most powerfully invaded the field of international finance, creating an atmosphere of extreme instability not only of the financial system itself, but also of the global economic system.